BIROKRASI DAN PELAYANAN PUBLIK - Dann Sugandha1 (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2006)
In 1987 Mr. Wilson said, â€œit is the object of administrative study to discover: first, what government can properly and successfully do; second, how it can do these proper things with utmost possible efficiency and at the least possible cost, either of money or of energyâ€. Our Indonesian government seeks strategies how it can properly and successfully serve the public. For this purpose, it releases Public Service Law. However, the first draft of the law is not based upon public interest. It is merely government initiative for the sake of governmental task completion. Several experiences including those of local governments do not take into account the fact that organization is a social system which has a lot of aspects as well as subsystems to be considered. Without considering these aspects, service institutions will hardly satisfy their clients. This writing shows the nature of organization and the principles to be implemented in order that public services can be delivered successfully.